A Comparative Study of the Educational Rights of Foreign Citizens in the Legal System of Iran and France - Elham Irajizadeh (Comparative Education Society of Iran ( CESIR), 2020)
The rights of foreign nationals are enshrined in all international treaties and accepted by most countries around the world. Nevertheless, these rights have been challenged in the Middle East over the past four decades due to the escalation of political and religious conflicts, wars and the migration of millions to other countries, the purpose of this paper is to compare the educational rights of foreign nationals in the Iranian and French legal systems.The method of research is comparative and selection of countries is based on targeted sampling. The structured search method was used to collect data and the data analysis method was directed content analysis. The research findings show that there are similarities between the French and Iran legal systems in terms of accepting international treaties - in which the educational rights of foreign nationals are clearly recognized. The main differences between these legal systems are the lack of a clear law on the practical implementation of the educational rights of foreign nationals for about forty years, the multiplicity of law codification centers for foreign nationals and lack of attention to role of mothers in issuing birth certificates for children in Iran and lack of clarity of educational laws relating to foreign nationals in France. Based on research findings, Iranian legislators are encouraged to review the laws related to the educational rights of foreign nationals, given the need to harmonize laws with the new developments in societies, as well as international law.